Surgical Site Infection Arising from the Operating Room - GÜL, ASİYE; Şengül, Tuba; Kirkland-Kyhn, Holly (W.B. Saunders Co-Elsevier Inc., 2025)
Many intraoperative risk factors contribute to the development of SSIs. Infection prevention interventions are the most critical way to reduce surgical site infections. Preventing SSIs will reduce associated morbidity, mortality, and health care costs. Prevention of SSIs in operating rooms should be a top priority. All surgical team members should prioritize taking preventive measures to reduce the risk of infection for every surgical patient.
Keywords: Infection Control; Intraoperative Practices; Operating Room; Patient Safety; Surgical Site Infection